Comparative Analysis: The Scholarly Culture of The Abbasid and Fatimid Dynasties - Andi Lifiani Ansar; Susmihara Susmihara; Abdurrahman Sibghatullah; Darmawan Darmawan (Universitas Islam Negeri Sumatera Utara, 2026)
This article examines the comparison of scientific culture between the Abbasid Dynasty and the Fatimid Dynasty, two great caliphates that significantly influenced the development of Islamic science. The Abbasid Dynasty was known for establishing Baitul Hikmah, which became an intellectual centre for advancements in astronomy, mathematics, medicine, and philosophy. Conversely, the Fatimid Dynasty, through the establishment of Al-Azhar, contributed to the field of education, particularly in Ismaili theology and religious philosophy. This study aims to compare the two dynasties regarding their roles in the development of science, focusing on their approaches to both natural and spiritual sciences. The comparative analysis found that although both dynasties made significant contributions to the scientific realm, they differed in their scientific orientation, influenced by their respective political and theological contexts. This research provides insight into the intellectual legacy of both dynasties and their impact on Islamic civilisation.